The effect of environmental influence on learning yoga to improve attention and concentration in learning disabled children. - Vijayalakshmi, P.; Ali Patel JM, Asgar (International Journal of Psychosocial Rehabilitation, 2024)
Environment influences the behaviour at different levels. These environments are included associal settings, built environments and informational environments. Learning Disability is adisorder in one or more of the fundamental psychological processes connected incomprehending the use of language, spoken and written. Apart from genetic factors, learningdisability is influenced by various environmental factors. This study investigated the effect ofenvironmental influence on learning yoga to improve attention and concentration in learningdisabled children. This single blind randomized controlled trial was carried out among 55children with learning abilities. The participants were divided into three groups, control groupwith 12 participants, experimental group I (without modified environment) with 24 participantsand experimental group II (with modified environment) consisting of 19 participants.Intervention training program was given for three weeks, with 15 sessions. Letter cancellationtest (1&2) and digit span test (Wechsler intelligence test) were used to measure the level ofattention problem and to measure the level of concentration. There was a significant differencein attention and concentration for learning disabled children between pre and post scores in theexperimental groups for both letter cancellation test and digit span test (P